A Biofunctional Perspective on Learning Environments - Alverson, Ryan (Frontiers in Psychology, 2015)
This paper proposes that the principles of learning, as highlighted by Bransford and colleagues, require biological grounding. This process essentially amounts to the facilitation of, and development of, an enriched capacity for ongoing biofunctional activity (OBA)—physical biology in action. The learning sciences’ principles of active learning, i.e., accessing prior understanding, organizing knowledge through schemas, and self-monitoring are psychological-understanding vehicles that work only in the ground of biofunctional (deep) understanding. Biofunctional understanding is a form of understanding that rises out of OBA. In this sense, biofunctional understanding juxtaposes and inherently complements psychological understanding. Without biofunctional understanding, psychological understanding becomes synonymous with superficial understanding. By contrast, in the illuminating context of biofunctional understanding, psychological understanding enables accomplishments of the kind enjoyed by experts in the rich and deep, metaphorically speaking, experiences of their respective fields of specialization. In this perspective article, I show how and why the psychological principles of active learning are ready for grounding in biofunctional understanding.